Natriuretic peptide pathways in heart failure in the context of the analysis of the mechanism of action and potential usages of sacubitril/valsartan - Babkiewicz-Jahn, Kamila; Matuszewska, Justyna; Szymańska, Adrianna; Wilanowska, Wiktoria; Oleksak, Izabela; Maliszewska, Karolina; Załęska, Natalia (Journal of Education, Health and Sport, 2024)
Introduction and purpose Heart failure has become a civilization disease, affecting 1-2% of the world's population. It is a condition with various etiologies and phenotypes. The annual mortality rate due to heart failure is approximately 10%, with organ dysfunction caused by hypoperfusion and sudden cardiac death being the leading causes of death. The aim of this study is to present current knowledge of heart failure, focusing on its pathophysiology, and the mechanism of action and applications of sacubitril/valsartan. Material and methods The following review was based on articles from the PubMed and Google Scholar databases. Key search terms included pathophysiology of heart failure; natriuretic peptide pathways; treatment of heart failure; sacubitril/valsartan. Conclusions Heart failure is a syndrome marked by the activation of various neurohormonal systems such as the renin-angiotensin-aldosterone system (RAAS), the sympathetic nervous system (SNS) and natriuretic peptides (NP). Historically, the therapeutic approach has focused on reducing RAAS activity and SNS activity. In recent years, increasing attention has been given to potential benefits associated with the NP system. Following disappointing outcomes from studies involving neprilysin (NEP) inhibitors, administered alone or in conjunction with an ACE inhibitor and vasopeptidase inhibitors, there have been findings with the pharmacological class termed ARNI (angiotensin receptor and NEP inhibitors). Sacubitril/valsartan has proven to be an effective and safe treatment that reduces the need for hospitalization, enhances the quality of life and longevity of patients with chronic HFrEF.